EFFECTIVENESS OF THE ADVENTURE OF TIMUN EMAS GAME IN IMPROVING THE READING SCORE OF INFORMATICS ENGINEERING STUDENTS - Yusniarsi Primasari (JOSAR (Journal of Students Academic Research), 2020)
One of the things that is very important to support the success of facing Asian Economic Community (AEC) is mastery of English. From the pretest in Informatics Engineering students conducted by researcher in January 2020, the average result was 50.17%. So it can be concluded that their reading comprehension skills are not good enough. On the other hand, There are several media to increase interest in reading. One form of learning media is educational games. Games are an interactive application that involves the relationship between humans and computers and humans and humans. The Adventure of Timun Emas is a game that contains reading comprehension learning. In certain parts English text and questions are inserted which require the player to answer the question in order to continue the game. This study adopted a pre-experimental design. The significance of the difference in mean change is determined by precise statistics such as the dependent T-test. From the results of calculations using the t-test found that the t-value obtained was 7,028, while the required critical t-value at p> .05, the level of significance of the two tailed test is 2.069 (df = 23), p> .01 significant level of two The tailed test was 2.807 (df = 23), p> .001, the significant level of the two tailed test was 3,768 (df = 23). The results of the data in this study indicate that there is a difference in results between the scores on the pre test and post test. This can be seen in the table of student scores on the pre test and post test. So it can be said that students taught by this game achieve better reading comprehension than those taught by printed text